Digital Transformation of Social Welfare Services in Madiun Regency - Hariyani, Nunik; Murti, Endang; Jayadi; Azzahra , Azizah Choirunisa (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2026)
This study intends to analyze the condition of social welfare in Madiun Regency by referring to the 2024–2026 Regional Development Plan (RPD) document. The main focus of the study includes the challenges of poverty alleviation, empowerment of vulnerable groups, the effectiveness of social welfare policies, and the role of digitalization and integration of social data in inclusive social services. This study uses a qualitative-descriptive approach with document analysis as the main method, supported by secondary data from government institutions and scientific references. The results of the study indicate that although the local government is strongly committed to improving social welfare governance, structural problems such as data inequality, limited human resource capacity, and minimal digital integration continue to hamper the program's effectiveness. On the other hand, digitalization and the utilization of integrated social data present strategic opportunities to create increasingly adaptive and inclusive social services. This study recommends strengthening the regional social information system, increasing the capacity of the apparatus, and multi-party collaboration as further steps to accelerate the achievement of equitable social welfare in Madiun Regency.